Ramesh's dilemma : dealing with variable EMI - Barua, S. K. (SAGE Knowledge. Cases., 2017)
The financial crisis of 2007-08 originated in indiscriminate lending by housing finance companies to borrowers who were in no position to pay back the amount borrowed. The delinquencies arose when the EMIs went up due to rising interest rate and the price of homes declined. Variable rate of interest often catches borrowed completely unprepared. A part of the blame lies with the housing finance companies that do not explain the implications to the borrowers at the time of loan sanction. The case is based on the actual experience of an HNI (High Net-worth Individual) who is unwittingly caught in the web of high EMI by a bank. He faces the devils choice. Choose he must though between the options presented by the situation. The case is amenable to meaningful discussion on policy prerogatives available to ensure that such skirmishes with unwary borrowers are avoided.